Inclisiran, Low-Density Lipoprotein Cholesterol and Lipoprotein (a) - Katsiki, Niki; Vrablik, Michal; Banach, Maciej; Gouni-Berthold, Ioanna (Pharmaceuticals (Basel, Switzerland), 2023)
Dyslipidemia treatment is of major importance in reducing the risk of atherosclerotic cardiovascular disease (ASCVD), which is still the most common cause of death worldwide. During the last decade, a novel lipid-lowering drug category has emerged, i.e., proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors. Apart from the two available anti-PCSK9 monoclonal antibodies (alirocumab and evolocumab), other nucleic acid-based therapies that inhibit or "silence" the expression of PCSK9 are being developed. Among them, inclisiran is the first-in-class small interfering RNA (siRNA) against PCSK9 that has been approved by both the US Food and Drug Administration (FDA) and the European Medicines Agency (EMA) for the treatment of hypercholesterolemia. Importantly, inclisiran therapy may improve low-density lipoprotein cholesterol (LDL-C) target achievement by offering a prolonged and significant LDL-C-lowering effect with the administration of only two doses per year. The present narrative review discusses the ORION/VICTORION clinical trial program that has been designed to investigate the impact of inclisiran on atherogenic lipoproteins and major adverse cardiac events in different patient populations. The results of the completed clinical trials are presented, focusing on the effects of inclisiran on LDL-C and lipoprotein (a) (Lp(a)) levels as well as on other lipid parameters such as apolipoprotein B and non-high-density lipoprotein cholesterol (non-HDL-C). Ongoing clinical trials with inclisiran are also discussed.
Keywords: atherosclerotic cardiovascular disease; proprotein convertase subtilisin/kexin type 9 inhibitor; low-density lipoprotein cholesterol; lipoprotein (a); inclisiran